Políticas de formação do pedagogo para atuação em espaços não escolares: o projeto político pedagógico da Autarquia Municipal do Ensino Superior de Goiana- PE - Cabral, Angela Ninfa Mendes de Andrade (2013)
This paper presents results of research conducted on the Pedagogical Political Project (PPP) of pedagogy degree course of the Municipality Municipal Higher Education of Goiás. This study aimed to analyze the teacher's training policies in official documents dealing with guidelines for performance of this professional in the non-school spaces, expressed in the curricular components of the initial training, through the teaching of the course political project. The text initially presents the scenario of the research describing the historicity of Goiana-PE municipality and the City Municipality of Higher Education of Goiás (AMESG) representative of the municipal institutions of higher education. In the scenario of the discussions about teacher training in the national context, it highlights the resistance movement against the creation of the Higher Education Institutes and the Superior Normal Course, this time stems from the strengthening of the degree course in pedagogy based on teaching. We approach the formation of the contemplated professor at the National Education Plan - PNE (2001-2010) and (2011-2020), the National Plan of Basic Education Teacher Training (PARFOR) and National Education Conference - CONAE (2010 and 2014) . Elected to Freirean continuing education category in the context of problem-based education to support the initial training of teacher in performance in non-school spaces. The debate on how the appointment of formal, non-formal and informal, founded the phrase "non-school spaces" which is based on our research. The methodology used was based on qualitative research, with the content analysis method, through the analysis of documents in the official texts of Opinions CNE / CP 5/2005, CNE / CP 03/2006 and in the CNE / CP No. 1, of May 15, 2006, and the Pedagogical Political Project of the degree course in pedagogy. From the study the training proposal in the course content presented curriculum components that include training of teacher for teaching activities in non-school spaces, spread over graduation, with theoretical and practical timetable established in the interdisciplinary context, and worked in methodological activities differentiated, promoting training under the aegis of the quest for knowledge of the discussions in the field of teacher training, based on the needs and social demands.